Integrated vertical aquaponics monitoring system using hibiscus sense with favoriot platform - Abdul Ismail Abdul Rani; Zhe, Bryan Jong Li; Nur’ain Farhah Suhardi; Mohd Shafiq Afnan Ali; Mohd Shahril Osman; Chee, Fuei Pien; Floressy Juhim (Penerbit Akademi Baru, 2025)
Aquaponics combines aquaculture and hydroponics, where fish and aquatic animals are grown in conjunction with soil-less plant cultivation in a circulated environment. Vertical aquaponics typically utilizes the nutrient film technique (NFT) method, employing pipes to continuously stream water to each channel, providing nutrients, water and oxygen to the plants. This project aims to develop a real-time monitoring system for the vertical aquaponics setup, using Hibiscus Sense along with Arduino Mega to measure pH, total dissolved solids (TDS) and water temperature to establish the optimal conditions for Bak Choy growth. All data is uploaded to the Favoriot IoT platform, which includes a dashboard to visualize the information. Results demonstrate a positive correlation between TDS and plant growth, indicating that plants efficiently utilize water nutrients for their development. The linear line values (R) for TDS and growth rate are close to 1.0, with respective values of 0.9234 and 0.9384, underscoring a strong relationship between TDS and plant growth. The ideal conditions for optimal Bak Choy growth are a high TDS value, ranging from 220 to 270 ppm and a pH value of 7.5. Additionally, maintaining a cool water temperature between 26°C and 29°C prevents plant shrinkage due to hot weather. The findings clearly indicate that TDS has a pronounced influence on the growth of Bak Choy, while temperature and pH values exhibit a relatively minor impact.